THE EFFECT OF LAMTORO LEAF FLOUR (Leucaena leucocephala) IN FEED ON THE GROWTH OF TILAPIA (Oreochromis niloticus) - Fadilatul Mukaromah; Kiki Haetami; Aulia Andhikawati; Roffi Grandiosa (Jurusan Perikanan dan Kelautan, 2024)
Tilapia is favored for its rapid growth and adaptability to diverse aquatic environments, making it a widely cultivated fish. In fish farming activities, feed provides the largest contribution to the total production cost. So that farmers must use alternative feed to reduce feed costs. One alternative feed for tilapia that is easy to obtain, affordable and sustainably available is lamtoro leaves. The aim of this research was to determine the effect of adding lamtoro leaf flour to feed at different concentrations on the growth of tilapia (O. niloticus). The average weight of tilapia at the beginning of the study was 5,7 grams. This research was conducted for 40 days starting in May until June 2023, taking place in Kertayasa Village, Cijulang District, Pangandaran Regency. The method used in this research was an experimental method using a completely randomized design (CRD) with 4 treatments and 3 replications, namely treatment A: 100% commercial feed (control), treatment B: commercial feed + 5% lamtoro leaf flour, treatment C: commercial feed + 10% lamtoro leaf meal, and treatment D: commercial feed + 15% lamtoro leaf meal. Parameters observed included daily growth rate (SGR), absolute length growth, and water quality. The results indicated a significant effect (P<0.05) on the daily growth rate (SGR) by incorporating lamtoro leaf flour into the feed. The highest treatment, observed in treatment C at 50%/day, resulted in the maximum absolute length growth of 4.63 cm. The water quality parameters during the study were in the proper range for the life of tilapia (O. niloticus). Providing lamtoro leaf flour in feed does not have a negative effect on growth and water quality. Keywords: Tilapia fish, lamtoro leaf meal, growth.